PROPHETIC INTELLIGENCE: Construct Development and Empirical Test for Its Role in The Perception of Unethical Conduct among Indonesian Goverment Employess - Adz Dzaky, Hamdany B.; Budiharto, Sus; Kurniawan, Irwan Nuryana; Riyono, Bagus (Asosiasi Psikologi Islam (API) Himpsi, 2005)
The current study is a part of a continous study on prophetic intelligence. The current study reports the construct building of prophetic intelligence. Prophetic intelligence is an integrated and holistic intelligence, which is developed from Islamic text. The dimensions that represent prophetic intelligence consist of intellectual intelligence, pyschological intelligence (emotion and adversity) and spiritual intelligence. The new construct is translated into a new measure called Prophetic Intelligence Scale. The resulte show an early empirical support for its contruct validity. A positive significant intercorrelations among four dimensions were found. Items were loaded into four different mentioned dimensions. The report also intelligence workshop in the perception of unethical conducts among goverment employees in Indonesia. Practical implications and suggestions for future research are discussed. Key words: Prophetic Intelligence, adversity, emotional, spiritual, intellectual, unethical conducts.